2012
DOI: 10.3390/ijms13078615
|View full text |Cite
|
Sign up to set email alerts
|

Green Extraction of Natural Products: Concept and Principles

Abstract: The design of green and sustainable extraction methods of natural products is currently a hot research topic in the multidisciplinary area of applied chemistry, biology and technology. Herein we aimed to introduce the six principles of green-extraction, describing a multifaceted strategy to apply this concept at research and industrial level. The mainstay of this working protocol are new and innovative technologies, process intensification, agro-solvents and energy saving. The concept, principles and examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
782
0
37

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,388 publications
(827 citation statements)
references
References 11 publications
8
782
0
37
Order By: Relevance
“…The cost of SC-CO 2 extraction process has restricted the applications to certain specialized fields such as decaffeinated coffee preparation industries [63] . The main drawbacks remain its high initial investment and difficulties to perform continuous extractions [64] . However, ultrasonic and microwave extraction gave the higher phenolic content.…”
Section: Effect Of Extraction Methods On Radical Scavenging Activitymentioning
confidence: 99%
“…The cost of SC-CO 2 extraction process has restricted the applications to certain specialized fields such as decaffeinated coffee preparation industries [63] . The main drawbacks remain its high initial investment and difficulties to perform continuous extractions [64] . However, ultrasonic and microwave extraction gave the higher phenolic content.…”
Section: Effect Of Extraction Methods On Radical Scavenging Activitymentioning
confidence: 99%
“…The recent studies have shown that the ultrasound-assisted extraction of can enhance the extraction efficiency through acoustic cavitation and some mechanical effects (Chemat et al, 2012(Chemat et al, , 2004Rostagno et al, 2003). Acoustic cavitation can disrupt cell walls facilitating solvent to penetrate into the plant material and allowing the intracellular product release.…”
Section: Introductionmentioning
confidence: 99%
“…In connection with green extraction of natural products, this definition can be altered as follows: "Green extraction is based on the discovery and design of extraction processes which will reduce energy consumption, allows use of alternative solvents and renewable natural products, and ensure a safe and high quality extract/product" [2].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, all cosmetic, perfume, biofuel, food, pharmaceutical, or fine chemical industries, use extraction procedures such as maceration, decoction, infusion, percolation, pressing, steam or hydro-distillation, and soxhlet extraction. Active principles or their precursors are extracted by pharmaceutical industries by conventional methods or modern technologies [2].…”
Section: Introductionmentioning
confidence: 99%